Cultural and physiological studies of Pleurotus ostreatus strain (DMRP-30) suited to Kerala - G, Heera; Amelinora, Tariang; Sreeja, S J; Johnson, Joy Michael; Radhakrishnan, N V (Mushroom Research, 2023)
Experiments were conducted to assess the optimum conditions viz., media, temperature and pH for mycelial growth of Pleurotus ostreatus. The media tested for mycelial growth were PDA (Potato Dextrose Agar), MEA (Malt Extract Agar), OMA (Oatmeal Agar), CA (Carrot Agar) and YEMA (Yeast Extract Mannitol Agar). All the media were found suitable for mycelial growth while the maximum growth was observed in PDA and identified as the best media. Liquid broths of the above said media were also tested for optimal mycelial biomass production of the oyster mushroom. The optimum temperature for the mycelial growth of P. ostreatus was recorded at 30°C than 25℃ and 20℃. The ideal pH for mycelial growth was tested at  different pH viz., 4, 4.5, 5, 5.5, 6, 6.5, 7 and 7.5. The maximum mycelial growth of P. ostreatus was supported by PDA at pH 7 and 7.5 while the least supportive pH was 4.